2004
DOI: 10.1096/fj.03-0648fje
|View full text |Cite
|
Sign up to set email alerts
|

Loss of vagally mediated bradycardia and bronchoconstriction in mice lacking M 2 or M 3 muscarinic acetylcholine receptors

Abstract: The presence of multiple muscarinic acetylcholine receptor (mAChR) subtypes in the heart and lung, combined with the lack of mAChR subtype-selective ligands, have complicated the task of identifying the mAChR subtypes mediating cardiac slowing (bradycardia) and airway narrowing (bronchoconstriction) due to vagal innervation. To determine which of the five mAChRs are responsible for the cholinergic control of heart rate and airway caliber in vivo, we performed experiments on mutant mice lacking the two prime ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 39 publications
4
76
0
2
Order By: Relevance
“…The lack of capsaicin reactivity is probably due to the absence of sensory nerve cell bodies in the cultured tracheal preparation. Thus, in the present organ culture assay EFS responsiveness in the mouse tracheal segments is essentially cholinergic in accordance with the lack of response to vagal stimulation in muscarinic M3 receptor-deficient mice (M3-/-mice) (Fisher et al 2004). …”
Section: Discussionsupporting
confidence: 69%
“…The lack of capsaicin reactivity is probably due to the absence of sensory nerve cell bodies in the cultured tracheal preparation. Thus, in the present organ culture assay EFS responsiveness in the mouse tracheal segments is essentially cholinergic in accordance with the lack of response to vagal stimulation in muscarinic M3 receptor-deficient mice (M3-/-mice) (Fisher et al 2004). …”
Section: Discussionsupporting
confidence: 69%
“…The M2AchR mediates negative feedback inhibition of acetylcholine release from parasympathetic nerve terminals in the airways (9), and its inhibition or absence promotes airway responsiveness to vagal stimulation (8,31). Furthermore, we have observed that the airways of female estrogen receptor-␣-deficient mice are male-like (i.e., more sensitive than those of wild-type females to methacholine aerosol) and that this phenotype is associated with decreased M2AchR expression and function (5).…”
Section: Discussionmentioning
confidence: 99%
“…The M2AchR is responsible for negative feedback regulation of acetylcholine release in the (9), and mice genetically deficient in this receptor display enhanced airway reactivity to cholinergic and vagal stimulation (8). Hence, pulmonary M2AchR protein levels were determined in naïve male and female mice to determine if differences in M2AchR expression might underlie the in vivo sex differences in airway responsiveness.…”
Section: Ajp-lung Cell Mol Physiolmentioning
confidence: 99%
“…The pathway delineated by genetic, physiological and pharmacological studies involved the activation of M 2 muscarinic receptors and the dissociation of the inhibitory heterotrimer with the G βγ activating GIRK channels in the SAN [4750]. However the GTP bound inhibitory G α subunit can also inhibit adenylate cyclase and reduce levels of cAMP reducing I f [51].…”
Section: G-protein Gated Inwardly Rectifying Potassium (Girk) Currentmentioning
confidence: 99%